2008
DOI: 10.1152/ajpregu.00875.2007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interval versus continuous training on cardiorespiratory and mitochondrial functions: relationship to aerobic performance improvements in sedentary subjects

Abstract: The goal of the study was to determine the effects of continuous (CT) vs. intermittent (IT) training yielding identical mechanical work and training duration on skeletal muscle and cardiorespiratory adaptations in sedentary subjects. Eleven subjects (6 men and 5 women, 45 +/- 3 years) were randomly assigned to either of the two 8-wk training programs in a cross-over design, separated by 12 wk of detraining. Maximal oxygen uptake (Vo2max) increased after both trainings (9% with CT vs. 15% with IT), whereas only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

30
256
2
18

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(306 citation statements)
references
References 55 publications
30
256
2
18
Order By: Relevance
“…Some studies, however, have suggested that HIT leads to improvements in both aerobic and anaerobic fitness [8] and improves endurance performance to a greater extent than endurance training alone [9]. For example, Daussin et al [10] found that maximal oxygen uptake (VO2max) increases were higher for untrained men and women who participated in an 8-week HIT program (15%) than they were for untrained participants undertaking an endurance training programme (9%). High-intensity interval training has also been reported to be more effective than continuous, steady-state exercise training for inducing fat loss in men and women, despite requiring considerably less total energy expenditure during training [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies, however, have suggested that HIT leads to improvements in both aerobic and anaerobic fitness [8] and improves endurance performance to a greater extent than endurance training alone [9]. For example, Daussin et al [10] found that maximal oxygen uptake (VO2max) increases were higher for untrained men and women who participated in an 8-week HIT program (15%) than they were for untrained participants undertaking an endurance training programme (9%). High-intensity interval training has also been reported to be more effective than continuous, steady-state exercise training for inducing fat loss in men and women, despite requiring considerably less total energy expenditure during training [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Mas a comparação direta do perfil fisiológico, em resposta ao exercício de fase constante em ambas as intensidades (PCR e VC) ainda não foi descrito. Essa informação descreveria, ou não, a tendência de similaridade na magnitude das repostas cardiorrespiratória e metabólica, pressupondo assim paridade nas respostas centrais e periféricas que, de acordo com Murias, Kowalchuk 14 e Daussin, Zoll 15 , são determinantes taxa oxidativa e da tolerância ao exercício nesta zona de intensidade.…”
Section: Introductionunclassified
“…Improvements in the oxidative potential of skeletal muscle is associated with a number of complex structural and morphological alterations, leading to an increase in mitochondrial content (Hoppeler et al, 1973), increase in metabolic enzymes (Gollnick & Saltin, 1982), oxidative fibre-type transformations (Inbar et al, 1981), enhanced capillary density (Daussin et al, 2008) and improved conduit and microvascular function (Lash & Bohlen, 1992;Rakobowchuk et al, 2008). Although mitochondrial function, independent of content may be increased by exercise training (Conley et al, 2013); the increase in mitochondrial content (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there is now good evidence demonstrating that exercise-induced mitochondrial biogenesis is modulated via PGC-1α dependant mechanisms (Calvo et al, 2008;Leick et al, 2010;Leick et al, 2008;Little et al, 2011;Safdar et al, 2011;Uguccioni and Hood, 2011;Zhang et al, 2014). Exercise capacity and performance has shown to be strongly associated with muscle mitochondrial content in both animal and human models (Daussin et al, 2008;Fitts et al, 1975) and is associated with improved risk factors for a variety of chronic diseases (Bishop-Bailey, 2013). Furthermore, mitochondrial dysfunction may be associated with the pathophysiology of cardiovascular disease (Wang et al, 1999;Wisloff et al, 2005), aging (Figueiredo et al, 2008) and muscle atrophy (Romanello et al, 2010).…”
Section: Introductionmentioning
confidence: 99%